The Study of Characteristics of Successful Asnafpreneurs in Southern Malaysia - Munahar, Muslihah Mohd; Badarudin, Ismadi Md; Harun, Norazman (Information Management and Business Review, 2024)
The study explores a characteristic of successful asnafpreneurs to address the number of registered asnafpreneurs seeking aid more than the number of successful asnafpreneurs produced in Southern Malaysia. However, the current industry can still not completely produce an independent business owner based on the Asnaf title. The study aims to determine successful entrepreneurs’ internal and external characteristics in Southern Malaysia. A quantitative method was used in this study. Respondents were chosen using the non-probability sampling method. SPSS software was used for data analysis. Descriptive analysis (frequency and percentage) and hypothesis testing (chi-square test, correlation, and regression) were utilized to solve the research topic. Study finds that internal factors and external factors play an important role in asnafpreneurs success. Chi-square Test analysis revealed that Pearson’s significant value was at the 0.00 level. This indicates that it is less than 0.05 at this level. This test successfully rejects H0, which means there is no correlation between internal factors with a successful characteristic of asnafpreneur and there is no correlation between external factors with a successful characteristic of asnafpreneur. Other authors may study the other geography parts and new challenges for asnafpreneurs to succeed in the future.